2020
DOI: 10.1103/physrevd.102.061701
|View full text |Cite
|
Sign up to set email alerts
|

Form factors with two operator insertions and the principle of maximal transcendentality

Abstract: We present the first calculations of two-point two-loop form factors (FFs) with a two identical operators insertion in maximally supersymmetric Yang-Mills theory. In this article, we consider the supersymmetry protected half-BPS primary and unprotected Konishi operators. Unlike the FFs of a single operator insertion of the half-BPS primary, the FFs involving two half-BPS operators are found to contain lower transcendentality weight terms in addition to the highest ones. Moreover, in contrast to Sudakov FFs, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Since form factors involve both local operators and asymptotic on-shell states, they contain important information of both on-shell amplitudes and anomalous dimension of local operators. This has inspired many studies that generalize amplitudes techniques to form factors and also use form factors to study the spectrum problem of generic operators [34][35][36][37][38][39][40][41][42][43][44]. A state-of-the-art pedagogical review for form factors in N = 4 SYM can be found in [45].…”
Section: Introductionmentioning
confidence: 99%
“…Since form factors involve both local operators and asymptotic on-shell states, they contain important information of both on-shell amplitudes and anomalous dimension of local operators. This has inspired many studies that generalize amplitudes techniques to form factors and also use form factors to study the spectrum problem of generic operators [34][35][36][37][38][39][40][41][42][43][44]. A state-of-the-art pedagogical review for form factors in N = 4 SYM can be found in [45].…”
Section: Introductionmentioning
confidence: 99%
“…In refs. [119,120], it has been shown that the conjecture also fails to hold true for two-point FF with two operators insertion. In view of this, we investigate whether there is any similarity between the HT weight terms of the scalar and pseudo-scalar FF as computed in this article and that of mSYM theory.…”
Section: Behaviour Of Leading Transcendentality Weight Termsmentioning
confidence: 99%
“…JHEP01(2022)189 F cotβ for the pseudo-scalar Higgs boson production. The corresponding one-loop two-point scalar FF in mSYM [120] with two operator insertion of half-BPS primary contain different kinematic coefficients.…”
Section: Behaviour Of Leading Transcendentality Weight Termsmentioning
confidence: 99%
“…In refs. [118,119], it has been shown that the conjecture also fails to hold true for two-point FF with two operators insertion. In view of this, we investigate whether there is any similarity between the HT weight terms of the scalar and pseudo-scalar FF as computed in this article and that of mSYM theory.…”
Section: Behaviour Of Leading Transcendentality Weight Termsmentioning
confidence: 99%
“…For instance, the one-loop finite remainders contain three weight 2 polylogarithms, Li 2 (−x), Li 2 (1/(1 + y)) and Li 2 (1/(1 + z)), with the coefficients F cotβ for the pseudo-scalar Higgs boson production. The corresponding one-loop two-point scalar FF in mSYM [119] with two operator insertion of half-BPS primary contain different kinematic coefficients. for the process q + q → φ + φ as a function of the scaling variable x for positive (left panel) and negative (right panel) values of cos(θ).…”
Section: Behaviour Of Leading Transcendentality Weight Termsmentioning
confidence: 99%